2003
DOI: 10.1007/s11663-003-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen reduction of oxidized nickel concentrates

Abstract: Thermal gravimetric analysis was used to investigate the weight change of Ni/Cu/Co calcines upon heating in an inert as well as hydrogen atmosphere. The two calcines investigated contained approximately 50 wt pct combined of hematite and magnetite in addition to sulfides of Ni, Cu, Co, and Fe. Mass spectrometry was used to analyze the gas species evolved during heating and reduction.The calcine samples are 100 pct less than 100 m with hematite/magnetite rims around a central sulfide core. When heating the calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The reduction experiments were carried out in a thermal gravimetric analysis unit (SETARAM TGA-92) with a detection limit of 10 g and a maximum heating rate of 30 • C/min (Crowe and Utigard, 2003). The samples, with sizes from 40 to 150 mg, were heated in alumina crucibles in a controlled gas environment.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction experiments were carried out in a thermal gravimetric analysis unit (SETARAM TGA-92) with a detection limit of 10 g and a maximum heating rate of 30 • C/min (Crowe and Utigard, 2003). The samples, with sizes from 40 to 150 mg, were heated in alumina crucibles in a controlled gas environment.…”
Section: Methodsmentioning
confidence: 99%
“…It could be possible to implement a heating stage before the calcine is sent to the electric furnaces, thereby collecting a large amount of SO 2 in a well-controlled and confined space, rather than to allow it to be released within the smelting furnace. Previous work (Crowe and Utigard [14] ) has shown that using a reducing atmosphere in a pretreating step can affect sulfate decomposition strongly.…”
Section: F Effect Of Cooling In the Electrostatic Precipitators (Espmentioning
confidence: 99%
“…This finding is consistent with the decompositions of the pure sulfates shown in Figure 9. Above this temperature, we might obtain local melting of the sulfide core with the formation of oxysulfide melts, [8,14,15] leading to accelerated kinetics and steady release of SO 2 by reaction. [6] The equilibrium constant for that reaction increases from 7250 at 773 K (500°C) to more than 10 10 at 1273 K (1000°C).…”
Section: G Simulation Of Separate Sulfate Removal Step Prior To Smelmentioning
confidence: 99%